2021
DOI: 10.3390/ijerph18147641
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Usability, and Credibility of an Intelligent Activity-Based Client-Centred Training System to Improve Functional Performance in Neurological Rehabilitation: An Exploratory Cohort Study

Abstract: (1) Background: technology-based training systems are increasingly integrated in neurorehabilitation but are rarely combined with a client-centred task-oriented approach. To provide a low-cost client-centred task-oriented system, the intelligent activity-based client-centred task-oriented training (i-ACT) was developed. The objective was to evaluate the usability, credibility and treatment expectancy of i-ACT, and the motivation towards i-ACT use in rehabilitation over time. Additionally, this study will evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…In this study, we found a very high adherence towards i-ACT training despite voluntary participation, i.e. 97.92%, which confirms the results from our cohort study [ 24 ]. This percentage might have been even higher because the reasons to miss an i-ACT therapy session were doctor appointments, hospital visits and family-related activities (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, we found a very high adherence towards i-ACT training despite voluntary participation, i.e. 97.92%, which confirms the results from our cohort study [ 24 ]. This percentage might have been even higher because the reasons to miss an i-ACT therapy session were doctor appointments, hospital visits and family-related activities (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…amount of practice), amount of repetitions (amount of practice), number of targets reached (from which a therapist can derive the level of difficulty), and the percentage of compensational movements (from which a therapist can derive the level of difficulty). i-ACT also has the potential to increase therapy dosage without major financial burden and negative side events as no adverse events or increase of fatigue were reported towards the additional use of i-ACT, no interference of additional i-ACT training to conventional care is found, and i-ACT is considered a low-cost system [ 24 ]. Also, during the COVID-19 pandemic, a secured online platform is developed so all results can be consulted by therapists from a distance which creates opportunities for the independent use of i-ACT in rehabilitation or even implementation in the person’s home environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that neurological rehabilitation needs to be varied. Therapy with modern technologies increases the motivation of patients [26][27][28][29]. Several elements can help to increase motivation: game mechanics (including scoring), results feedback (including leveling up), and game fun [18].…”
Section: Introductionmentioning
confidence: 99%